Monitorization of NGAL, Creatinine and Renal Blood Flow in the Follow-up of Acute Kidney Injury in Intensive Care - (:unkn) unknown (YERKURE TANITIM & YAYINCILIK HIZMETLERI A S, 2021)
Objective: Acute Kidney Injury (AKI) and subsequent renal failure are the leading causes of morbidity and mortality in the intensive care unit (ICU). In this study, it was planned to compare Neutrophil Gelatinase-associated Lipocalin (NGAL) and creatinine values in patients diagnosed with AKI and to determine the effect of renal dose dopamine use on renal blood flow, development of chronic renal failure (CRF) and mortality. Methods: This prospective study was planned with 35 patients developed AKI in the ICU of Bakirkoy Dr. Sadi Konuk Training and Research Hospital. The patients were randomized into 2 groups as 18 patients who received dopamine treatment with the recommendation of the cardiology clinic and 17 patients who did not receive dopamine treatment. Urea, creatinine and NGAL plasma levels were compared between groups. Results: There was no difference between the groups in terms of age, gender and AKI stage. The 0th, 24th hour results and 24-hour changes of urea, creatinine and NGAL values of dopamine patient, who took dopamine, were found to be similar to those of patients who did not take dopamine. A significant positive correlation was found between the 24-hour change in creatinine value and the 24-hour change in NGAL (r=0.374; p<0.05). There was no significant change in the diameter and flow of renal arteries between measurements in patients who received dopamine. The rates of patients who regain normal kidney functions, develop CRF or develop mortality between the two groups were found to be similar. Conclusion: Treatment results of AKI developing in ICU are not satisfactory. Low-dose dopamine treatment has no effect on patient outcomes in these patients. NGAL is a biomarker that has the ability to show renal damage at an early stage. Serial measurement of NGAL concentration during ICU stay may benefit the clinician in early diagnosis and follow-up of AKI.
Keywords: Acute Kidney Injury; NGAL; Creatinine; Renal Doppler Ultrasonography; Intensive Care Unit; GELATINASE-ASSOCIATED LIPOCALIN; LOW-DOSE DOPAMINE; ACUTE HEART-FAILURE; CARDIAC-SURGERY; EARLY-DIAGNOSIS; BIOMARKERS; URINARY; DYSFUNCTION; MORTALITY; PREDICTOR